2013
DOI: 10.5805/sfti.2013.15.1.057
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Environment-conscious Consumer Attitudes towards Eco-friendly Product and Artificial Leather Fashion Product Purchase Intentions

Abstract: : This research examines the environmental consciousness of fashion consumer attitudes towards eco-friendly products and artificial leather purchase intentions. The survey was conducted from March 11 to March 15 2012 and all respondents had at least once experience of purchasing fashion items made of artificial leather. A total of 426 subjects were used in the dataset; the statistical analysis methods were frequency analysis, factor analysis, reliability analysis and multiple analysis. The results are as follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
1
1
0
1
Order By: Relevance
“…Maichum, Parichatnon, and Peng [10] showed that attitude has most significant positive relationship with consumer's purchase intention. Environmental consciousness reported a significant positive effect on environmental attitude and purchase intention towards green products, which supported the findings of [42], [43]. Furthermore, the empirical finding reported that environmental knowledge was the strongest predictor of environmental attitude for green products and followed by purchase intention.…”
Section: Hypotheses Testingsupporting
confidence: 81%
“…Maichum, Parichatnon, and Peng [10] showed that attitude has most significant positive relationship with consumer's purchase intention. Environmental consciousness reported a significant positive effect on environmental attitude and purchase intention towards green products, which supported the findings of [42], [43]. Furthermore, the empirical finding reported that environmental knowledge was the strongest predictor of environmental attitude for green products and followed by purchase intention.…”
Section: Hypotheses Testingsupporting
confidence: 81%
“…Huang et al (2014) menemukan bahwa attitude toward green brand (sikap terhadap produk hijau) berpengaruh secara signifikan terhadap purchase intention (niat beli). Park et al (2013) menemukan bahwa kesadaran lingkungan secara signifikan mempengaruhi sikap maupun niat beli. Menurut Kotler dan Keller (2009:137) minat beli adalah perilaku konsumen yang timbul sebagai respon yang menunjukkan keinginan pelanggan untuk melakukan pembelian pada sebuah objek.…”
Section: Pendahuluanunclassified
“…Park et al (2013). Moreover, the environmental attitude construct was adapted from Maichum et al (2016) and was based on three metrics.…”
mentioning
confidence: 99%